La souveraineté ou les souverainetés ? Réflexions sur les relations entre souveraineté de l’État et souveraineté de la nation - Chęciński, Remigiusz; Departout, Alexandre; Mądry, Tymoteusz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The study attempts an analysis of the relationship between the concepts of state and nation sovereignty. The thesis has been proposed that state sovereignty could be regarded as a derivation of nation sovereignty. While attempting to approve of the proposed thesis, the authors describe the relationship between both institutions by referring to their origins. In the light of concepts of sovereignty, the relationship between state and international law is presented from a philosophical perspective. Approving the proposed thesis, the authors conclude that regardless of whether state sovereignty derives from nation sovereignty or not, the two concepts refer to different backgrounds which can be seen both in their origins and contemporary realities.